2013
DOI: 10.1097/igc.0b013e31828c166d
|View full text |Cite
|
Sign up to set email alerts
|

Detection of MicroRNA as Novel Biomarkers of Epithelial Ovarian Cancer From the Serum of Ovarian Cancer Patient

Abstract: Serum miR-132, miR-26a, let-7b, and miR-145 could be considered as potential candidates as novel biomarkers in serous ovarian cancer. Also, serum miRNAs is a promising and useful tool for discriminating between controls and patients with serous ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(85 citation statements)
references
References 26 publications
4
81
0
Order By: Relevance
“…miR-145, located at 5q32, was found to be decreased in various types of cancers such as breast, 13 colon, 14,15 lung, 16 liver, 17 bladder, 18 pituitary, 19 B cell, 20 ovary 4,14,21 and prostate. 22 To date, a cohort of genes related to different cancer pathways have been identified as its target genes.…”
mentioning
confidence: 99%
“…miR-145, located at 5q32, was found to be decreased in various types of cancers such as breast, 13 colon, 14,15 lung, 16 liver, 17 bladder, 18 pituitary, 19 B cell, 20 ovary 4,14,21 and prostate. 22 To date, a cohort of genes related to different cancer pathways have been identified as its target genes.…”
mentioning
confidence: 99%
“…The expression of circulating miRNA precursor let-7b was reported to be diverse among various cancer types. Let-7b was found to be upregulated in breast tumors (29) and downregulated in ovarian cancer (30). The same trend was found for the expression of circulating let-7c, which was increased in esophageal cancer (31) but decreased in nasopharyngeal carcinoma patients with poor prognosis (32).…”
Section: Discussionsupporting
confidence: 58%
“…An increasing number of studies have revealed the vital role microRNAs play in ovarian cancer carcinogenesis [14][15][16][17][18][19][20][21]. However, Most of these studies have been performed on ovarian tissue samples.…”
Section: Introductionmentioning
confidence: 99%